2016
DOI: 10.1073/pnas.1608069113
|View full text |Cite
|
Sign up to set email alerts
|

Precision glycocalyx editing as a strategy for cancer immunotherapy

Abstract: Cell surface sialosides constitute a central axis of immune modulation that is exploited by tumors to evade both innate and adaptive immune destruction. Therapeutic strategies that target tumor-associated sialosides may therefore potentiate antitumor immunity. Here, we report the development of antibody-sialidase conjugates that enhance tumor cell susceptibility to antibodydependent cell-mediated cytotoxicity (ADCC) by selective desialylation of the tumor cell glycocalyx. We chemically fused a recombinant sial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
347
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 362 publications
(358 citation statements)
references
References 49 publications
11
347
0
Order By: Relevance
“…Approaches are now being explored for targeted removal of glycocalyx components to enhance NK cell-mediated tumour killing. For example, therapeutic conjugates consisting of the HER2-specific antibody trastuzumab fused to a recombinant sialidase removed sialylated glycans from tumour cells and induced potent NK cell cytotoxic activity 84 .…”
Section: Physical Microenvironment Of the Tumourmentioning
confidence: 99%
“…Approaches are now being explored for targeted removal of glycocalyx components to enhance NK cell-mediated tumour killing. For example, therapeutic conjugates consisting of the HER2-specific antibody trastuzumab fused to a recombinant sialidase removed sialylated glycans from tumour cells and induced potent NK cell cytotoxic activity 84 .…”
Section: Physical Microenvironment Of the Tumourmentioning
confidence: 99%
“…Therapeutic interventions designed to target tumour-associated sialosides or block inhibitory Siglec function may provide a promising new avenue for cancer immunotherapy. To this end, a recent study showed that recombinant sialidase fused to the human epidermal growth factor receptor 2 (HER2)-specific antibody trastuzumab desialylated tumour cells in a HER2-dependent manner, reduced tumour cell binding to inhibitory NK cell Siglecs, and enhanced ADCC [30]. Yet another approach has been to synthesise small sialic acid derivatives that bind with high affinity to Siglec-7, although it remains unclear whether these molecules can block Siglec receptor function in cytotoxicity assays [31].…”
Section: The Cancer Cell Glycocalyxmentioning
confidence: 99%
“…Meanwhile, increased sialylation was often associated with poor prognosis in cancer patients [13]. A recent study showed that desialylation of cancer cells reduced natural killer cell inhibitory sialic acid-binding Ig-like lectin (Siglec) receptors, and increased natural killer cell activating receptor natural killer group 2D (NKG2D), suggesting a precise sialylation editing method for cancer targeting immune therapy [26]. …”
Section: Introductionmentioning
confidence: 99%